SURVEY AND EFFORTS TO IMPROVE MITIGATION ABILITY FOR DISABILITY STUDENTS IN GORONTALO CITY - Reski Fauzi Duwingik; Della Nawarita Kasim; Dewi Ayu Ayu; Moh Aristo Dano; Intan Noviantari Manyoe (Universitas Muhammadiyah Gorontalo, 2019)
The condition of Gorontalo City has a high level of vulnerability to earthquake hazards, for this reason an understanding of earthquakes needs to be done early, especially for children with disabilities. This study aims to determine the level of understanding of earthquake mitigation for students with disabilities in SDLB Gorontalo, especially the blind, deaf, and autism and to find the efforts to improve the mitigation ability of disability students. The method that will be used in this study is the survey method with the instrument used in the form of a questionnaire. The samples in this study were 34 people with disabilities in SDLB of Gorontalo City consisting of blind, deaf and autism students. The results obtained are the level of understanding and ability of students for earthquake mitigation is very low (not good category) where for blind people is 3.5%, while deaf is 1.6%, and autism is 0.1%. For this reason, efforts need to be done to improve the ability of disabilities with cheerful learning media such as cheerful music for the visually impaired, attractive images for the deaf, and for autism given attractive images accompanied by gifts for what they do to improve their abilities and their learning enthusiasm. Keyword: Disability , Students, Ability, Earthquake, Mitigation, Gorontalo.